2018
DOI: 10.1002/jae.2668
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of direct and iterated multistep conditional forecasts

Abstract: Summary When constructing unconditional point forecasts, both direct and iterated multistep (DMS and IMS) approaches are common. However, in the context of producing conditional forecasts, IMS approaches based on vector autoregressions are far more common than simpler DMS models. This is despite the fact that there are theoretical reasons to believe that DMS models are more robust to misspecification than are IMS models. In the context of unconditional forecasts, Marcellino et al. (Journal of Econometrics, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Early studies on multi-step prediction using direct approach are done with auto-regression model for forecasting and estimating indicators in economic area [17]. In various studies, results of direct approach are comparatively analyzed against recursive approach using nonlinear data [18], and it is concluded that the direct approach shows better results for long target sequences in terms of prediction error, parameter estimation error, and efficient finite data samples [19]. A study for vehicular route prediction defines mobility patterns as consecutive series of road segment selections.…”
Section: A Direct Approach For Multi-step Predictionmentioning
confidence: 99%
“…Early studies on multi-step prediction using direct approach are done with auto-regression model for forecasting and estimating indicators in economic area [17]. In various studies, results of direct approach are comparatively analyzed against recursive approach using nonlinear data [18], and it is concluded that the direct approach shows better results for long target sequences in terms of prediction error, parameter estimation error, and efficient finite data samples [19]. A study for vehicular route prediction defines mobility patterns as consecutive series of road segment selections.…”
Section: A Direct Approach For Multi-step Predictionmentioning
confidence: 99%
“…They can be customized to produce a forecast for multiple intervals ahead. McCraken et al [27] talk about VAR models in detail, focusing on their utilization in direct and recursive forecasting. Further in his paper, McCraken demonstrated a comparison of two methods for conditional forecasting and concluded that the recursive method acts better than the direct method [27].…”
Section: Related Workmentioning
confidence: 99%
“…Marcellino et al (2006), Taieb and Atiya (2016)), empirical investigations in macroeconometrics have uncovered the opposite for both unconditional and conditional forecasts (e.g. Marcellino et al (2006), McCracken and McGillicuddy (2019)). To the best of our knowledge, no previous study has compared recursive and direct forecasting models in the context of EPF.…”
Section: Electricity Price Modelling and Forecasting Approachesmentioning
confidence: 99%